Pemanfaatan Kain Perca dan Pemasaran Online sebagai Sarana untuk Meningkatkan Kreativitas Kewirausahaan bagi Peserta Didik SMA Negeri 21 Bekasi (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2021)
Abstract: the purpose of community service is that students have skills in the recycling of used cloth waste, especially the use of patchwork and students can produce creative works and have an entrepreneurial spirit. The methods used are observation, interview, and training. Based on the training that has been carried out the following results are obtained: 1) Students have been able to assemble patchwork into crafts (bross). 2) Students are able to make attractive packaging in marketing. 3) Students are able to market bross through social media. 4) Students are able to motivate themselves in making patchwork crafts. 5) Students show an interest in entrepreneurship.